2013
DOI: 10.1038/cddis.2013.325
|View full text |Cite
|
Sign up to set email alerts
|

Activated microglia mediate synapse loss and short-term memory deficits in a mouse model of transthyretin-related oculoleptomeningeal amyloidosis

Abstract: Oculoleptomeningeal amyloidosis (OA) is a fatal and untreatable hereditary disease characterized by the accumulation of transthyretin (TTR) amyloid within the central nervous system. The mechanisms underlying the pathogenesis of OA, and in particular how amyloid triggers neuronal damage, are still unknown. Here, we show that amyloid fibrils formed by a mutant form of TTR, A25T, activate microglia, leading to the secretion of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and nitric oxide. Further, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 44 publications
1
33
2
Order By: Relevance
“…Regardless of the mechanism(s) of action, our current findings are in contrast to the microglial inhibition and neuroprotection reported in many previous rodent studies using similar doses of minocycline (30–90 mg/kg; studies referenced above as well as more recent findings by Ma et al, ; Reinebrant et al, ; Azevedo et al, ; Kobayashi et al, ; Yin et al, ; Peng et al, ). The present observations are in accord, however, with those of two recent studies reporting increased cell death specifically in layer V of the mouse sensorimotor or somatosensory cortex following neonatal minocycline treatment (Ueno et al, ; Arnoux et al, ).…”
Section: Discussioncontrasting
confidence: 98%
“…Regardless of the mechanism(s) of action, our current findings are in contrast to the microglial inhibition and neuroprotection reported in many previous rodent studies using similar doses of minocycline (30–90 mg/kg; studies referenced above as well as more recent findings by Ma et al, ; Reinebrant et al, ; Azevedo et al, ; Kobayashi et al, ; Yin et al, ; Peng et al, ). The present observations are in accord, however, with those of two recent studies reporting increased cell death specifically in layer V of the mouse sensorimotor or somatosensory cortex following neonatal minocycline treatment (Ueno et al, ; Arnoux et al, ).…”
Section: Discussioncontrasting
confidence: 98%
“…Two inflammatory cytokines (IL-1β and IL-6) implicated in neuronal apoptosis (Azevedo et al, 2013; Guadagno et al, 2015) are known to be regulated by ERβ engagement in brain microglia (Saijo et al, 2011). For this reason, we examined IL-1β (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent animal study showed that the injection of amyloid-β oligomers leads to depressive-like phenomena in mice (Ledo et al , 2013). Also, the deposition of Aβ in the brain leads to microglial activation, increased pro-inflammatory markers, and reduced neurotrophic support (Azevedo et al , 2013). These changes are observed in both AD and LLD subjects (Thorsell et al , 2010; Naismith et al , 2012).…”
Section: Discussionmentioning
confidence: 99%